Effect of Alternating Magnetic Field Intensity on Microstructure and Corrosion Properties of Deposited Metal in 304 Stainless Steel TIG Welding - Jinjie Wang; Jiayi Li; Haokai Wang; Zan Ju; Juan Fu; Yong Zhao; Qianhao Zang (Metals)
Stainless steel, due to its exceptional comprehensive properties, has been widely adopted as the primary material for liquid cargo tank containment systems and pipelines in liquefied natural gas (LNG) carriers. However, challenges such as hot cracking, excessive deformation, and the deterioration of welded joint performance during stainless steel welding significantly constrain the construction quality and safety of LNG carriers. While conventional tungsten inert gas (TIG) welding can produce high-integrity welds, it is inherently limited by shallow penetration depth and low efficiency. Magnetic field-assisted TIG welding technology addresses these limitations by introducing an external magnetic field, which effectively modifies arc morphology, refines grain structure, enhances penetration depth, and improves corrosion resistance. In this study, TIG bead-on-plate welding was performed on 304 stainless steel plates, with a systematic investigation into the dynamic arc behavior during welding, as well as the microstructure and anti-corrosion properties of the deposited metal. The experimental results demonstrate that, in the absence of a magnetic field, the welding arc remains stable without deflection. As the intensity of the alternating magnetic field intensity increases, the arc exhibits pronounced periodic oscillations. At an applied magnetic field intensity of 30 mT, the maximum arc deflection angle reaches 76°. With increasing alternating magnetic field intensity, the weld penetration depth gradually decreases, while the weld width progressively expands. Specifically, at 30 mT, the penetration depth reaches a minimum value of 1.8 mm, representing a 44% reduction compared to the non-magnetic condition, whereas the weld width peaks at 9.3 mm, corresponding to a 9.4% increase. Furthermore, the ferrite grains in the weld metal are significantly refined at higher alternating magnetic field intensities. The weld metal subjected to a 30 mT alternating magnetic field exhibits the highest breakdown potential, the lowest corrosion rate, and the most protective passive film, indicating superior corrosion resistance compared to other tested conditions.